"Traubenmadonna" w kulturze winiarskiej nad Mozelą w Niemczech (wybrane przykłady) = "Traubenmadonna" in the Moselle region`s wine culture in Germany (chosen examples) - Krawiec, Angelika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article there was described an image of Madonna showed with vine attributes in wine-making culture by the river Moselle in Germany in the context of European culture. Use of symbols of vine bush, grape and wine is strictly rooted in Christian tradition since time immemorial. The fruit of grapevine and wine made from it symbolise the sacrifice and blood of Savior, which was shed for world`s sins. Images of Traubenmadonna refer to this symbol. Examples of these kinds of works which are placed in Moselle Valley certify cult of the Virgin Mary`s meaning and specificity in wine sector.
Keywords: Traubenmadonna; Maria (Matka Jezusa Chrystusa); winogrono; winorośl; wino; krew Chrystusa; Zbawiciel; Biblia; średniowiecze; renesans; Mozeli Dolina; Saint Mary; grape; grapevine; wine; Christ`s blood; Savior; Bible; Middle Ages; Renaissance; Moselle Valley